Exposure to multiclass pesticides among female adult population in two Chinese cities revealed by hair analysis - Peng, Feng-Jiao; Hardy, Emilie M.; Mezzache, Sakina; Bourokba, Nasrine; Palazzi, Paul; Stojiljkovic, Natali; Bastien, Philippe; Li, Jing; Soeur, Jeremie; Appenzeller, Brice M.R. (Environment international, 2020)
•“Hair analysis was used to assess exposure of 204 Chinese women to multiclass pesticides.•71 pesticides and 23 metabolites were found in at least one subject.•In each subject the number of detected chemicals ranged from 25 to 50.•38 biomarkers presented significantly different concentration between the 2 cities.•Age, BMI, cooking frequency and regions affected concentrations of pesticides in hair.” The high use of pesticides worldwide and the constant exposure of humans to these toxic-by-design chemicals have drawn the attention on the possible consequences on human health. However, information on the exposure of the general population to pesticides remain very limited in most countries, especially in urban areas. In the present work, hair analysis was conducted to investigate the exposure of 204 urban women living in two Chinese cities (Baoding and Dalian) to 110 pesticides and 30 metabolites of the following families: organochlorines, organophosphates, carbamates, pyrethroids, neonicotinoids, phenylpyrazoles, acid herbicides, urea herbicides and azoles. Results showed that 71 pesticides and 23 metabolites were found in the hair samples, with concentrations ranging up to 1070 pg/mg in hair. In each hair sample, the number of detected chemicals ranged from 25 to 50, demonstrating the cumulative exposure to pesticides among Chinese women in the studied regions. The concentrations of 38 chemicals (e.g., p-nitrophenol, diethyldithiophosphate, λ-cyhalothrin, permethrin, carbendazim and tebuconazole) were significantly different between women in Baoding and Dalian, indicating the regional differences in exposure to pesticide. Using a multiple regression analysis, we found that concentrations of a few dominant pesticides were associated with age, body mass index (BMI), cooking frequency and regions. These results can provide baseline information on exposure of female adult Chinese population to multiple pesticides and support future studies focused on the health effects associated with pesticide exposure.